Synthesis of Existentialist and Phenomenological Approaches in Educational Management Leadership - Modeong, Tirta Safirah; Dewi, Ni Putu Saras; Jaenudin, Dadang (Journal of Educational Management Research, 2025)
This study aims to explore the synthesis of existentialism and phenomenology in educational leadership to develop a more inclusive and humanistic leadership model. The method used is library research, analyzing relevant literature on educational leadership, existentialism, and phenomenology. The main findings indicate that by integrating these two philosophical approaches, educational leaders can better understand and appreciate the lived experiences of individuals within the school community and provide each member with the freedom and responsibility to find meaning in learning. This approach encourages the creation of a more reflective, empathetic educational environment and is oriented toward character development rather than just academic outcomes. This study makes a theoretical contribution to the development of a humanistic perspective in educational leadership. Its practical implications include creating an inclusive and supportive school culture and increasing individual empowerment. These findings also open the door to further research to test the practical application of this synthesis in a broader educational context.